Long noncoding RNA GHET1 promotes the development of bladder cancer - Li, Lin-Jin; Zhu, Jian-Long; Bao, Wen-Shuo; Chen, Da-Ke; Huang, Wei-Wen; Weng, Zhi-Liang (International journal of clinical and experimental pathology, 2014)
In spite of the advances in the diagnosis and treatment of bladder cancer, the prognosis of bladder cancer remains relatively poor. As a result, it is vital to identify novel diagnostic and prognostic marker of bladder cancer. A growing volume of literature has implicated the vital role of long noncoding RNA in the development of cancer. GHET1, a recently identified lncRNA, was initially characterized in gastric cancer. However, its role in bladder cancer remains largely unknown. In this study, we demonstrated that GHET1 was upregulated in bladder cancer tissues compared to adjacent normal tissues and its over-expression correlates with tumor size, advanced tumor and lymph node status, and poor survival. GHET1 knockdown suppressed the proliferation and invasion of bladder cancer cells in vitro. In the meantime, inhibition of GHET1 reversed the epithelial-mesenchymal-transition in bladder cancer cell line. Taken together, our study suggests that the potential use of GHET1 as a prognostic marker and therapeutic target of bladder cancer.